Evaluation of the Potential of Brazilian Red Propolis in the Acceleration of Healing in Surgical Wounds - de Medeiros, Gerard Vicente D.; da Silva Teófilo, Tiago; Salatino, Antonio; Negri, Giuseppina; Jara, Carmen E.P.; Viana, Geysa Almeida; Costa, Wirton Peixoto; Freitas, Carlos Iberê Alves; de Menezes, Manuela Costa; de Morais, Marcos C. B.; Moura, Gabriela Hémylin Ferreira; Rodrigues, Victor Hugo Vieira; et al. (Natural Products Journal, The, 2021)
Background: The use of red propolis has antimicrobial, anti-inflammatory, antioxidant activity results, and provides local conditions that optimize events involved in the healing process, accelerating tissue repair. Objective: To evaluate the chemical composition, antioxidant activity, cytotoxic effects, and healing potential of Red Propolis Hydroethanolic Extract (RPHE) on the surgical wounds of cats submitted ovarisalpingohisterectomy. Methods: Chemical analyses of RPHE were carried out using HPLC-DADESI-MS/MS. Antioxidant activity was evaluated using the DPPH (2,2-diphenyl-1-picrilhydrazyl) method, and cytotoxicity was evaluated using the MTT colorimetric method. The healing effect of the extract was evaluated in 60 domestic cats (Felis catus) divided into three groups: GI: treated with topical application RPHE; GII: received topical application of commercial rifamycin-based solution, and GIII: treated with topical application of 0.9% NaCl physiological solution. Surgical wounds were evaluated for clinical, macroscopic, and histological aspects. Results: The RPHE showed 26 flavonoids and high antioxidant activity. Propolis extract had no cytotoxic effect on any of the cell lines tested. High cell viability percentages were observed, ranging from 80.0% to 94.4% for L929 fibroblasts and 78.0% to 91.5% keratinocytes (Hacat). Red propolis had a positive influence on the healing of wounds in cats submitted to ovarisalpingohisterectomy because it promoted less intense inflammatory response, rapid closure of the wound, early deposition of collagen and reepithelization. Conclusion: The RPHE presented rich in flavanoids, high antioxidant activity, did not exert cytotoxic effect and promoted the acceleration of healing of surgical wounds.
Keywords: flavonoids